Atrocity Accountability in the 21st Century: A World Turned Upside Down - David M. Crane (Washington University Global Studies Law Review, 2022)
Professor Leila Sadat was a central figure in creating the accountability paradigm, an age of accountability from 1993-2015, as well as a friend, colleague, and an inspiration to us all. Before the shadows of populism/nationalism set in, Professor Sadat was a steadfast advocate for the rule of law where tyrants, dictators, and thugs were held accountable. She remains so today, despite these new challenges of populism/nationalism. During the Age of Accountability, the beast of impunity was faced down, that terrible pariah fading before the bright light of justice. It was through her efforts during this time, among many of our other mutual friends and colleagues, that a new legal discipline was created, international criminal law. This is a particularly important step for mankind which had just emerged from the bloody 20th century and the destruction and ruin of tens of millions of humans at the hands of their own governments with little or no accountability. Despite this new “wonderland” we now face, Professor Sadat remains a true rock in the middle of the stream of history in facing down tyranny.